Exploring the influence of the surface resistance of nanoporous particles on molecular transport - Krutyeva, Margarita; Vasenkov, Sergey; Kärger, Jörg (Diffusion Fundamentals, 2007)
Molecular transport through the nanoporous particles, in particular, zeolite crystallites, is influenced both by intracrystalline diffusion and surface resistance. In comparison to zeolite crystallites with ideal structure, molecular transport in real-world zeolite particles may often be influenced by the surface barriers resulting from various defects at the surface of the crystallite. The potentials of the combined use of the pulsed field gradient NMR and dynamic Monte Carlo simulations for exploration of the surface permeability of nanoporous particles are demonstrated.